Inuit women working in the Nunavik justice system : a relational perspective on justice - Hervé, Caroline; Laneuville, Pascale (Études Inuit Studies, 2024)
The literature on how Inuit women relate to justice has thus far portrayed them largely as victims of various types of violence and in need of assistance. However, justice does not concern them only as victims, offenders, or affected family members, as many of them work in this field as crucial actors for their communities, providing people in difficulty with support and helping them navigate a complex structure. This article emphasizes the important role of Nunavik Inuit women today in maintaining community harmony. We also explore their views on the justice system and outline what an Inuit system of justice could look like today. Our research project used a participatory methodology, an ontological approach, and both qualitative and quantitative methods. Our results suggest that Nunavik justice is not simply a legal institution and should therefore be defined much more broadly and incorporate the moral principles of social responsibility and interdependence. La littérature concernant les rapports des femmes inuit avec la justice les a jusqu’à présent dépeintes essentiellement comme des victimes de divers types de violence ayant besoin d’aide. Cependant, la justice ne les concerne pas seulement en tant que victimes, délinquantes ou membres de la famille affectés. Aujourd’hui, nombre d’entre elles travaillent dans ce domaine en tant qu’actrices cruciales pour leur communauté, apportant un soutien aux personnes en difficulté et les aidant à s’orienter dans une structure complexe. Nous soulignons ici le rôle important que jouent aujourd’hui les femmes inuit du Nunavik dans le maintien de l’harmonie communautaire. Nous présentons également leur point de vue sur le système judiciaire et esquissons ce à quoi pourrait ressembler un système de justice inuit aujourd’hui. À cette fin, nous présentons les résultats d’un projet de recherche pour lequel nous avons mobilisé une méthodologie participative, une approche ontologique, ainsi que des méthodes qualitatives et quantitatives. Nos résultats suggèrent que la justice ...